Emotional Intelligence And Competence: Influence On Hospital Nurse Performance - Masitoh; Sanusi (Enrichment : Journal of Management, 2022)
Nurses are always faced with various demands and workloads so they need to have stable emotional intelligence in dealing with their daily work. The purpose of this study was to examine the effect of emotional intelligence and competence on the performance of nurses. The study was conducted at three public hospitals in Banten Province including RSUD dr. Drajat Prawiranegara, Banten General Hospital and Serang City Hospital used a quantitative approach, with a sample of 100 people. Based on the results of data analysis using SEM-PLS, emotional intelligence has the most dominant effect on nurse performance compared to competence. This study proves the importance of stable emotional intelligence to be able to support the achievement of maximum nurse performance